American pie : Band camp ; American pie : The naked mile. - Hilgenbrinck, Tad, 1981-; Kebbel, Arielle, 1985-; Earles, Jason; White, Johnny, 1981-; Schram, Jessy, 1986-; Talley, Steve, 1981-; Riddell, Brad; Lindsay, Erik; Rash, Steve; Nussbaum, Joe; Universal Pictures (Firm); Rogue Pictures; et al. (Universal City, CA Universal Pictures Home Entertainment, 2016)
Band camp: The "Stiffmeister" legend reaches outrageous new heights when the bad-boy antics of Stifler's younger brother get him sentenced to a summer at ... band camp!
The naked mile: When Erik Stifler realizes that he's the only Stifler family member who might graduate high school a virgin, he decides to live up to his legacy.
Title from container.
Anamorphic widescreen.
Band camp: Universal Pictures presents a Rogue Pictures production ; written by Brad Riddell ; directed by Steve Rash.
The naked mile: Rogue Pictures presents a Neo Art & Logic, Inc. production ; written by Erik Lindsay ; directed by Joe Nussbaum.
Band camp: Tad Hilgenbrinck, Arielle Kebbel, Jason Earles.
The naked mile: John White, Jessy Schram, Steve Talley.
Keywords: Greek letter societies -- Drama; College students -- Conduct of life -- Drama; Male friendship -- Drama; Comedy films; Drama; Feature films; Video recordings for the hearing impaired; DVD-Video discs